Understanding the Contributing Factors of School Violence and Intervention Strategies Used in the SADC Region: A Scoping Review Protocol - Gift Khumalo; Nosipho Faith Makhakhe; Bokang Nephtali Lipholo (E-Journal of Humanities, Arts and Social Sciences)
Access to quality education, as per the Southern African Development Community’s (SADC) vision is essential for improving the overall economic growth and development of the region. However, this vision is severely hindered by school violence, a pervasive contextual issue across multiple SADC countries. Guided by Arksey and O’Malley’s five-step framework, this proposed scoping review sought to explore the contextual factors that contribute to school violence and examine intervention strategies that have been used to mitigate school violence. Six databases will be used to search for empirical articles, including ProQuest, PubMed, Web of Science, Academic Search Ultimate, PsycINFO and MEDLINE Ultimate. Screening at the abstract, title and full-text level will be conducted by all authors, with further articles being searched on the research list of the final included full-text publications. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) will be used to report on the scoping review processes. It is hoped that this scoping review will contribute to the overall understanding of the contextual factors that contribute to school violence in the context of SADC and the intervention strategies used to curb this phenomenon. The scoping review will also identify gaps in knowledge in literature and gaps in the current intervention practices, as well as influence future research on school violence in the SADC region.